The Effect of Season and Dominance Hierarchy on Strategic Interaction Among Birds in Mixed-species Aggregation - Munipapa Reddy Ashok Kumar, Agnishikhe (Jihočeská univerzita, 2023)
The effect of the dominance hierarchy and the season was studied on different aspects of mixed-species bird aggregation at feeders, such as the group size, feeding propensity, and strategic interaction among birds. To achieve these goals two types of feeders namely: gauze ball feeders and bottle feeders were used. The study was conducted in winter accounting for the non-breeding season and spring for the breeding season in three sites around České Budějovice, Czech Republic.
The Effect of Season and Dominance Hierarchy on Strategic Interaction Among Birds in Mixed-species Aggregation
Keywords: feeding propensity; dominance inetractions; feeder experiment; interspecific interactions; dominance ranks; feeding propensity; dominance inetractions; feeder experiment; interspecific interactions; dominance ranks